Sanctified [videorecording (DVD)] - Bielinski, Daniel; Cornwell, Tiffany; Wheeler, Andrew E. (FilmRise, 2023)
A thrilling Western set in 1890 North Dakota, Sanctified tells the story of an outlaw rescued from death by a nun traveling the Badlands. A deep friendship develops as she nurses the man back to health in exchange for his guidance at a local church.